Demographic and Socioeconomic Determinants of Noma (Cancrum Oris) and Strategies to Reverse the Trend - Mujtaba Bala; Amidu Omotayo Sulaiman; Abdulrazaq Olanrewaju Taiwo; Ramat Oyebunmi Braimah; Adebayo Aremu Ibikunle; Abubakar Abdullahi Bello; Shafiu Isah Abdulazeez; Lukman Adeniran Olayemi; Rufai Jaafar; Abubakar Mohammad Kaura (Wolters Kluwer Medknow Publications, 2024)
Background: Noma is a major cause of mortality and morbidity in Nigeria and other sub-Saharan African countries with dire far-reaching consequences on the precarious health system and socioeconomic situation of the vulnerable population of the region. Aim: This study aimed to describe the demographic and socioeconomic determinants of noma patients and proffer workable strategies to check the trend. Materials and Methods: Relevant clinical data of the subjects such as demographics, socioeconomic factors, clinical outcome, and length of hospital stay were recorded and analyzed using SPSS version 25. Results: A total of 178 case records of patients managed with noma were included and there were 76 (42.7%) males and 102 (57.3%) females. The age range of the study subjects was 1-33 years with mean±SD of 6.23±4.63. The majority of the subjects 172 (96.6%) were from rural communities, farming 126 (70.8%) was the main source of income of the study subjects. All the subjects were from poor households with low socioeconomic status and most of the subjects 175 (8.3%) were not enrolled in formal education. Measles 81 (45.5%) and malnutrition 78 (43.8%) were the most common risk factors identified. Good clinical outcome was recorded with 23 days average length of hospital stay. Conclusion: Demographic and socioeconomic determinants play a crucial role in the occurrence of noma and attention to vulnerable age groups by removing health inequities, fair distribution of resources, and poverty alleviation and improving the living conditions of the affected people would lead to the eradication of the scourge.